Controlling Acid Sites in Atomically Precise Cu/Al2O3 Clusters for Selective Methanol Production from CO2 Hydrogenation - Jin, Seongmin; Lin, Yu-Cheng; Karakurt, Bartu; Nelis, Tom; Tanchev, Mark; Piveteau, Laura; Mensi, Mounir Driss; Bugaev, Aram; Safonova, Olga; Luterbacher, Jeremy S. (American Chemical Society, 2025)
Creating low-nuclearity moieties on the order of 10 metal atoms presents an opportunity to exert control over their electronic properties, thereby tuning their catalytic behavior. We designed an atomic cluster catalyst (Cu/MgOAl2O3) comprising small Al2O3 clusters in contact with Cu species via liquid-phase atomic layer deposition (ALD) with near-atomic precision. Upon the reduction of Cu in Cu/MgOAl2O3, direct interactions between Cu and Al atoms occurred in a low nuclearity cluster (Cu/Al2O3), leading to alterations in their electron densities. This interaction resulted in a reduced Lewis acidic strength of Al atoms on a basic MgO support compared with the strong Lewis acidity found from the bulk Al2O3-supported Cu catalyst (Cu/Al2O3). Modulating Lewis acidity in this way effectively tuned the adsorption strength of the reaction intermediates during the hydrogenation of CO2 to methanol, achieving a methanol selectivity of 59%. Moreover, Cu/MgOAl2O3 exhibited approximately 9 and 3 times higher space-time-yield (STY) compared to Cu/Al2O3 and Cu/MgO, respectively. In contrast, the strong binding of acetate and methoxy species on Cu/Al2O3 caused surface poisoning, limiting its methanol selectivity to 20%. This study establishes that the formation of small metal oxide clusters can introduce controlled complexity to active sites, offering a method for designing multifunctional catalysts.